Online Learning Challenges in School - Haerul Haerul; Andi Agustang; Andi Muhammad Idhan; Rifdan Rifdan (Universitas Negeri Makassar, 2021)
The concept of independent learning has been echoed and realized in the management of education in Indonesia, especially now that the Covid-19 pandemic has affected almost all aspects of human life. This research is intended to examine and analyze related to the application of learning from school. The type of research used is a qualitative approach. Data were collected through interviews, observation and documentation review. The data analysis technique was carried out by descriptive analysis, namely data reduction, data presentation, and drawing conclusions or verification. The results of the study indicate that in distance learning (PJJ) or online but in its implementation there are still polemics or challenges experienced by teachers including; lack of online teaching skills, lack of Learning Facilities, lack of teacher interaction with students. Therefore, it is necessary to improve the ability of teachers in the implementation of online learning through workshops and the provision of assistance for learning facilities in the form of smartphones for the underprivileged.